DINAMIKA PERUMUSAN UPAH MINIMUM KOTA BATAM TAHUN 2012-2013 - Winta Pratiwi; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted to analyze how the dynamic formulation ofMSEs in the City Btam 2012-2013. Formulation of MSEs in Batam year 2012-2013 experiencing tough debate advance of Trade Unions APINDO premises. Theproblem in this research is how the dynamic formulation of MSEs in the CityBtam years 2012-2013?This study is a qualitative study, the data collection techniques in thisstudy is a descriptive analysis. This study uses the documentation (observation)and key informant interviews together as objects of information that aims toachieve the goal to get the information in this study. Data used in this study areprimary data and secondary data obtained through direct observation andinterviews with key informants in this study.Based on the results of research conducted, it can be concluded that in thefield of employment one of the problems faced by workers from year to year is theissue of wages. MSE formulation dynamics always starts from labor discontentover their wages terimasehingga wage boards consisting of APINDO, laborunions and the government should review the formulation of policy formulationby considering several alternatives based on the results of a quantitative surveyKHL fluctuating and changing every year. Determination of minimum wagepolicy is a safety net (social safety net) to safeguard the welfare of workers andanticipate the decline of purchasing power imbalance diakibatkanoleh societywhich labor market (labor market disequilibrium) .Pemerintah as the mediatormust be considerate in the dynamics of SME policy formulation is due to theincrease in wages the minimum is too drastic to be detrimental to the company.Conversely rise too flat / ramps unfavorable workers, because the increase ininflation that will be lost by raising workers' welfare objectives will not beachieved.Key : formulation, policy, minimum wage town